Age-related decline in retinal function in marmosets - Takahiko Noro; Xiaoli Guo; Rika Kikuchi; Kenya Sato; Kazuhiko Namekata; Youichi Shinozaki; Chikako Harada; Terumi Yurimoto; Nanako Hashimoto; Keiko Moriya-Ito; Tadashi Nakano; Erika Sasaki; et al. (Scientific Reports)
Abstract Vision deterioration caused by natural aging have a detrimental impact on an individual’s quality of life, which has become a serious problem as the world’s population is aging rapidly. Rodents are the commonly used animal species to investigate the physiological aging process or to identify possible therapeutic targets. However, due to anatomical differences and their genetic distance to humans, translation of findings is sometimes complicated. In the present study, as a step toward aging study in vision using non-human primate marmosets, we examined the eyes of aged marmosets non-invasively. We found that the retinal response deteriorated along with the retinal structure in aged marmosets and the retinal peripheral region was more susceptible to aging. Moreover, the expression of the oxidative stress biomarker 4-HNE was increased in the serum of aged marmosets although no significant correlation was found between 4-HNE levels and the retinal thickness. Our study demonstrated that marmosets offer a promising translational model for the research of age-related vision declination.